"A New Hope for Asia"? Australia, the United States and the Promotion of Economic Development in Southeast Asia. (9th January 2018) - Ferns, Nicholas
Abstract : The Colombo Plan and Point Four program were programs that provided technical and economic assistance to the newly independent countries of Southeast Asia. They represented Commonwealth and American attempts to promote economic development in the region. This paper will investigate how these policies, which were framed by US policy‐makers and academics, were adopted in Australia. In so doing, it will demonstrate the ways that development was perceived as an important consideration in the foreign policies of both Australia and the United States. It will also examine the place of these programs in the Cold War and postcolonial world of the 1950s. As this paper will show, the interaction of these factors would affect Australian foreign policy for decades to come, revealing much about the complex nature of the Australian‐American relationship.